Tibial pilon fractures: management and evaluation of the outcome in mean and long term about 51 cases - Camara, Abdoulaye; Keita, Karinka; Doukoure, Mamady; Conde, Mamady S.; Balde, Abdoul K.; Camara, Fatoumata; Camara, Ibrahima M.; Bah, Amadou T.; Diallo, Mamadou M.; Diallo, Mamadou C.; Lamah, Leopoid (International Journal of Research in Orthopaedics, 2024)
Background: the management of tibial pilon fractures is a real challenge in our regions. Methods: This was a mixed study: dynamic from January 1 to December 31, 2013 involving 19 patients; retrospective from January 1, 2014 to December 31, 2018, covering 32 patients, received, treated and followed up for tibial pilon fracture in the Orthopedics-Traumatology department of the Donka university hospital center, Conakry Republic of Guinea. The clinical diagnosis was guided by the pain, functional impotence, a context of high trauma energy and confirmed by the X-ray of the ankle in antero-posterior and lateral views. The AO (association for Osteosynthesis) classification was used in our department. Results: The average age was 36.21 years old with male predominance, the sex ratio was 5.4. The road accidents were the mostly found (86.27%). The motorbicycles were the mostly involved; the osseous lesions the mostly found were the type C according to AO classification (56.86%), followed by type B (33.33%). The orthopaedical treatment (27.45%), and surgical (72.55%). The ankle arthrosis was the most complication found (27.45%). Conclusions: Tibial pilon fractures are rare but serious however the treatment depends on the anatomopathological type. The prognosis of these lesions remains always reverved in our context of lack of equipment in our hospitals.